ความคาดหวังและความพึงพอใจของนักท่องเที่ยวชาวไทย ที่มีต่อตลาดน้ำบางน้ำผึ้ง จังหวัดสมุทรปราการ: Expectation and Satisfaction of Thai Tourists for Bang Nam Peung Floating Market Samutprakarn - Homsud, Noppanon; Nilsaeng, Narisa (Asian Health, Science and Technology Reports, 2011)
This research’s purposes were to study the level of the expectation, the satisfaction of Thai tourists to Bang Num Peung floating market, Samutprakarn province and to compare the differences between the expectation and the satisfaction of Thai tourists to Bang Num Peung floating market, Samutprakarn province. The sample groups were 400 Thai tourists visiting Bang Num Peung floating market, Samutprakarn province by convenience sampling. Tools used in this research were questionnaires, statistical analysis of data employed was frequency, percentage, mean, standard deviation, and hypothesis test (t-test) The results found that the expectation level of Thai tourists visiting Bang Num Phueng floating market was at the high level. When it was considered in each category, the respondents paid attention in attractive things and the restaurant and the beverage at the highest level. While the satisfaction level of Thai tourists to Bang Num Peung floating market was general high. When each side was considered, it found that tourists focus at the high level on all seven sides; consisting of Public Relations, Service of Officer, Utility, Transportation, Safety, Price and Shop, and Souvenir Place. As for hypothesis testing, it was found that the expectation level of Thai tourists to Bang Num Peung floating market was significant higher than the satisfaction level at the 0.05 statistical levels.